Liouville-type theorem for the stationary fractional compressible MHD system in anisotropic Lebesgue spaces - Wenda Pei; Yong Zeng (Electronic Research Archive)
This paper is devoted to the study of the Liouville-type theorem of the stationary fractional compressible MHD systems in anisotropic Lebesgue spaces in $ \mathbb{R}^3 $. We showed that the solution is trivial when certain anisotropic integrability conditions are satisfied in terms of the velocity and the magnetic field components.